Implementation of Employee Engagement in Improving Productivity and Innovation in Startup Companies - Herikson Tampubolon; Olyvia Rosalia; Dodi Setiawan Riatmaja; Kholid Ansori; Lumastari Ajeng Wijayanti; Zainal Firdaus Wardhana (Maneggio, 2025)
This study explores the impact of employee engagement and productivity on innovation in startup companies. The research aims to understand how employee involvement, motivation, and productivity contribute to fostering innovation in a dynamic and competitive environment. A quantitative approach was used to analyze the relationship between these variables. The study highlights that employee engagement plays a crucial role in enhancing creativity, commitment, and job satisfaction, which in turn drive innovation. Similarly, higher productivity leads to improved efficiency and adaptability, enabling startups to remain competitive and innovative. The findings suggest that organizations with engaged and productive employees are more likely to develop new ideas, implement creative solutions, and sustain long-term growth. The study provides insights for startup leaders and managers, emphasizing the importance of cultivating a supportive work environment, offering professional development opportunities, and fostering a culture of collaboration. By implementing effective engagement and productivity strategies, startups can enhance innovation and maintain a sustainable competitive advantage.